Is a 10‐minute surgical scrub necessary in urologic prosthetic surgery? A randomized study of the effect of a 5‐ vs 10‐minute surgical scrub on bacterial colony counts in the genital skin. Issue 3 (22nd February 2019) - Malalasekera, Ashanya; Louie‐Johnsun, Mark; Wang, Audrey; van Diepen, Danielle C.; Gottlieb, Thomas; Chan, Lewis
Abstract: Aims: To determine the antiseptic efficacy on bacterial colony counts of a 5‐ vs 10‐minute surgical site scrub in urologic surgery. Methods: A prospective cohort study was conducted in 101 patients presenting for elective urological procedures. Patients were randomized to a 5‐ or 10‐minute groin scrub with Betadine (povidone‐iodine). Skin swabs were taken immediately after skin clipping and following routine painting with Betadine. A third swab was taken after the betadine skin scrub. Bacterial colony counts were reported as a number of colony‐forming units (CFUs). The primary outcome measure was a quantitative comparison of CFUs in the two arms. Results: Fifty‐three patients were randomized to a 5‐minute scrub and 48 to a 10‐minute scrub. After Betadine painting, CFUs were present in 38% of patients in the 5‐minute group (mean, 33.5 CFU) and in 27% of the 10‐minute group (mean, 45.4 CFU). Following the surgical scrub, only 7.5% of the 5‐minute group and 8.3% of the 10‐minute group had a measurable CFU count of greater than or equal to 1, and colony counts were low in both groups (5‐ minute group: mean, 1.5 CFU; 10‐minute group: mean, 2.0 CFU). There was no significant difference in CFUs following a 5‐ or 10‐minute scrub ( P = 0.28). Conclusions: The addition of a surgical skin scrub leads to a fourfold reduction in the skin CFU count compared with Betadine painting. However, there is no difference between the antibacterial effects of a 5‐ and 10‐minute scrub. A 5‐minute scrub may be sufficient in urologic prosthetic surgery.